A model describing pressure buildup in rough surfaces with partially filled gaps. Issue 1 (December 2014) - Mueller, Michael; Bubser, Florian; Ostermeyer, Georg‐Peter
Abstract Because of an ecological and economical need to reduce the application of lubricants, the tribological regime of starved lubrication in the field of mechanical engineering has gained importance during the last decades. In order to describe the respective processes properly, models should consider that the gap between the bodies is not fully but only partially filled with a fluid. Recently, the authors introduced a model which explicitly describes the fluid flow and its interaction with the buildup of pressures under these conditions [1]. This paper points out that the correlation between the filling ratio and a time‐ and space‐averaged pressure value is highly nonlinear. This is due to the fact that the system's load bearing character changes from being a local effect to a global effect, in particular near the fully filled regime. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)